Diet and Helicobacter pylori infection - Hołubiuk, Łukasz; Imiela, Jacek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Helicobacter pylori infection has accompanied man for thousands of years. In some infected patients, a complex and dynamic pathogen-host reaction triggers pathogenic pathways resulting in development, inter alia , of atrophic gastritis, peptic ulcer disease (both gastric and duodenal), gastric adenocarcinoma, and MALT lymphoma. Large-scale eradication therapy is associated with a rapid increase in antibiotic resistance, gut flora composition disturbances, and increased risk of development, inter alia , of paediatric infectious diarrhoeas, atopic diseases, and oesophageal adenocarcinoma. Our diet contains many substances with potent antibacterial activity against H. pylori . Dietary interventions enable a decrease in H. pylori colonisation and result in a decrease in gastritis prevalence, thus potentially lowering the risk of gastric adenocarcinoma development.